Human factor management for remote-control safety of maritime autonomous surface ships - Li, Xue (Nanyang Technological University, 2024)
Autonomous shipping is expected to be part of the maritime industry. There has been a lot of research on autonomous shipping safety from an engineering perspective, but human perspective research is limited and scattered. Therefore, this thesis aims to focus on remote control in autonomous shipping operations and comprehensively investigate potential human factors. Through qualitative data from published literature and expert judgments collected from the analytical survey, three studies are designed. The first study found that poor shore-based control center performance is a significant risk to autonomous shipping. The second study found that cognitive and mental factors are considered threatening to remote-control performance. The third study identified primary risk influential factors and proposed strategies focusing on regulatory improvements, fostering a supportive social environment, prioritizing human-machine interface design, developing competent leadership, and implementing health interventions. The research contributes to addressing the knowledge gap in understanding human factors in the autonomous shipping context, offering practical insights for maritime stakeholders.